2015
DOI: 10.1186/s40364-015-0041-4
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric acute myeloid leukaemia with the t(7;12)(q36;p13) rearrangement: a review of the biological and clinical management aspects

Abstract: The presence of chromosomal abnormalities is one of the most important criteria for leukaemia diagnosis and management. Infant leukaemia is a rare disease that affects children in their first year of life. It has been estimated that approximately one third of infants with acute myeloid leukaemia harbour the t(7;12)(q36;p13) rearrangement in their leukaemic blasts. However, the WHO classification of acute myeloid leukaemia does not yet include the t(7;12) as a separate entity among the different genetic subtype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(73 citation statements)
references
References 53 publications
1
70
0
2
Order By: Relevance
“…The correct maintenance of the higherorder chromatin structure is crucial for cellular health, and its alteration is an emerging factor in human cancer, including leukaemia [Bártová et al, 2000;Ballabio et al, 2009;Tosi et al, 2015]. Over the past decade or so, the observations obtained using microscope imaging and analysis of FISH data were further supported by the introduction of the chromosome conformation capture technique [Dekker et al, 2002] and its variants, such as the high-throughput chromosome conformation capture [Lieberman-Aiden et al, 2009].…”
Section: Concettamentioning
confidence: 90%
“…The correct maintenance of the higherorder chromatin structure is crucial for cellular health, and its alteration is an emerging factor in human cancer, including leukaemia [Bártová et al, 2000;Ballabio et al, 2009;Tosi et al, 2015]. Over the past decade or so, the observations obtained using microscope imaging and analysis of FISH data were further supported by the introduction of the chromosome conformation capture technique [Dekker et al, 2002] and its variants, such as the high-throughput chromosome conformation capture [Lieberman-Aiden et al, 2009].…”
Section: Concettamentioning
confidence: 90%
“…7,8 In 2006, von Bergh et al 9 reported that the translocation t(7;12) (q36;p13) was identified in about 30% of infant AML and associated with a poor outcome. [11][12][13][14][15] It involves heterogeneous breakpoints at 12p13 of the ETV6 gene (previously named TEL) and at 7q36, in which the MNX1 gene (motor neuron and pancreas homeo-box1, previously named HLXB9) has been identified as the partner gene. The translocation has not yet been included in the WHO classification for AML.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that accurate identification of t(7;12) would improve risk evaluation and therapy stratification for childhood AML. 11,12,[15][16][17] In the t(7;12)(q36;p13), the breakpoints on chromosome 12 are consistently between exons 1 and 3 at the 5 0 end of ETV6, whereas the breakpoints on chromosome 7 are more heterogeneous affecting band q36 in regions proximal to MNX1. 10 The translocation is often cryptic and most reliably detected using FISH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ведущее место среди опухолей детского возраста отводится острым лейкозам (30%), при этом 4/5 всех случаев острых лейкозов у детей приходится на острый лимфобластный лейкоз, 1/5 -на острый миелобластный лейкоз [9] (рис. 6).…”
Section: биологические особенности гемобластозовunclassified